PEMANFAATAN TUMBUHAN TYPHA LATIFOLIA SEBAGAI AGEN FITOREMEDIASI DALAM PENGOLAHAN LIMBAH CAIR - Maharani Shintya Putri; Elsa Septiani Rintho Miharjo, Septiana Kurniawati, Wima Rahayu Putri, Merlly Alfina Septiana, Endah (CV. ADIBA AISHA AMIRA, 2023)
Wastewater or effluent is the discarded water that originates from households, industries, and other public places, generally containing substances or materials that can be harmful to human health and disrupt the environment. Phytoremediation is an effort to use plants for waste decontamination. Typha latifolia usually thrives in shallow water and is an exploitative plant in its ability to clone rapidly and produce a large surface area of leaves, which contributes to its competitive and superior capabilities. The research method used a literature review by adopting the analysis of several articles. Reviewing documents by discussing and evaluating previous research on Typha latifolia phytoremediation, based on Table 1, it is explained that Typha latifolia plants are effective in absorbing heavy metals, such as mercury (Hg), chromium (Cr), cadmium (Cd), and lead (Pb), which are present in the sludge chemicals splashed in Porong Sidoarjo, including phenol. Table 2 explains that one of the uses of Typha latifolia plants is as a phytoremediation agent to reduce the levels of Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD). And based on Table 3, it is explained that one of the uses of Typha latifolia plants is as a phytoremediation agent in wastewater treatment. Typha latifolia plants are highly effective as phytoremediation agents in wastewater treatment, as they absorb ammonia levels in the waste. The influence of plant height is evident, as higher plants result in a faster reduction of ammonia concentration and a decrease in pollutant concentration in wastewater.